(untitled) (Global Journal of Computer Science and Technology, 2022)
Day by day the number of confirmed Covid-19 cases signif- icantly increases all over the world In India the second wave of coro- navirus has come back and created a disastrous impact On April 3rd India continuously recorded the highest number of daily cases globally according to Financial Times there was a scarcity of crematoriums and burial grounds due to the high number of corpses The outbreak of death cases was an unprecedented circumstance hence there was a shortage of medical necessities Prediction of death cases could help the govern- ment to manage the medical facilities such as beds and oxygen supply for the hospital